Evaluating the Usability of a Wearable Social Skills Training Technology for Children with Autism Spectrum Disorder - Kinsella, Ben G.; Chow, Stephanie; Kushki, Azadeh (Frontiers in Robotics and AI, 2017)
Affecting 1 in 68, autism spectrum disorder (ASD) is a complex neuro-developmental disorder characterized by social skill impairments. While prognosis can be significantly improved with intervention, few evidence-based interventions exist for social skill deficits in ASD. Existing interventions are resource-intensive, their outcomes vary widely for different individuals, and they often do not generalize to new contexts. Technology-aided intervention is a motivating, low-cost, and versatile approach for social skills training in ASD. Although early studies support the feasibility of technology-aided intervention, existing approaches have been criticized for teaching social skills through human-to-computer interaction, paradoxically leading to increased social isolation. To address this gap, we propose a system to help guide human-to-human interaction called Holli, a wearable technology to serve as a social skills coach for children with ASD. The Google Glass-based application listens to conversations and prompts the user with appropriate social responses. In this paper, we describe a usability study we conducted to determine the feasibility of using wearable technology to prompt children with ASD throughout social conversations. Fifteen children with ASD (mean age=12.92 2.33, verbal IQ=103.3 18.73) used the application while engaging in a restaurant-themed interaction with a research assistant. The application was evaluated on its effectiveness (i.e. how accurately the application responds), efficiency (i.e. how quickly the user and the application respond), and user satisfaction (based on a post-session questionnaire). All users were able to successfully complete the 10-turn exchange while using Holli. The results indicated the Holli accurately detected and recognized user utterance in real time. Participants reported positive experiences of using the application. To the best of our knowledge, this system is the first technology-aided intervention for ASD that employs human-to-human social coaching, and our results demonstrate the device is a viable medium for treatment delivery.